Hidden but Ubiquitous: The Pre-Rift Continental Mantle in the Red Sea Region - Sanfilippo, Alessio; Sani, Camilla; Rasul, Najeeb M. A.; Stewart, Ian C. F.; Vigliotti, Luigi; Widinly, Nawaf; Osemi, Ahmed; Ligi, Marco (Frontiers in Earth Science, 2021)
Volcanism in the western part of the Arabian plate resulted in one of the largest alkali basalt provinces in the world, where lava fields with sub-alkaline to alkaline affinity are scattered from Syria and the Dead Sea Transform Zone through western Saudi Arabia to Yemen. After the Afar plume emplacement (∼30 Ma), volcanism took place in Yemen and progressively propagated northward due to Red Sea rifting-related lithospheric thinning (initiated ∼27–25 Ma). Few lava fields were emplaced during the Mesozoic, with the oldest 200 Ma volcanic activity recorded in northern Israel. We report results from volcanic pipes in the Marthoum area, east of Harrat Uwayrid, where over a hundred pipes occupy a stratigraphic level in the early Ordovician Saq sandstones. Most of them are circular or elliptical features marked by craters aligned along NW-SE fractures in the sandstone resulting from phreatomagmatic explosions that occurred when rising magma columns came in contact with the water table in the porous sandstone host. These lavas have Sr-Pb-Nd-Hf isotopic compositions far from the Cenozoic Arabian alkaline volcanism field, being considerably more enriched in Nd-Hf and Pb isotopes than any other Arabian Plate lava ever reported. New K-Ar dating constrains their age from Late Cretaceous to Early Eocene, thus anticipating the Afar plume emplacement and the Red Sea rift. Basalt geochemistry indicates that these volcanic eruptions formed from low-degree partial melting of an enriched lithospheric mantle source triggered by local variations in the asthenosphere-lithosphere boundary. This mantle source has a composition similar to the HIMU-like enriched isotopic component reported in the East African Rift and considered to represent the lowermost lithospheric mantle of the Nubian Shield. The generated melt, mixed in different proportions with melt derived from a depleted asthenosphere, produces the HIMU-like character throughout the Cenozoic Arabian alkaline volcanism. Although apparently hidden, this enriched lithospheric component is therefore ubiquitous and widespread in the cratonic roots of the African and Arabian subcontinental mantle.